Deciphering miRNA signatures in axial spondyloarthritis: The link between miRNA-1-3p and pro-inflammatory cytokines - Prokopcova, Aneta; Baloun, Jiri; Bubova, Kristyna; Gregova, Monika; Forejtova, Sarka; Horinkova, Jana; Husakova, Marketa; Mintalova, Katerina; Cervenak, Vladimir; Tomcik, Michal; Vencovsky, Jiri; Pavelka, Karel; et al. (Heliyon, 2024)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that affects the spine and sacroiliac joints. Early detection of axSpA is crucial to slow disease progression and maintain remission or low disease activity. However, current biomarkers are insufficient for diagnosing axSpA or distinguishing between its radiographic (r-axSpA) and non-radiographic (nr-axSpA) subsets. To address this, we conducted a study using miRNA profiling with massive parallel sequencing (MPS) and SmartChip qRT-PCR validation. The goal was to identify differentially expressed miRNAs in axSpA patients, specifically those subdiagnosed with nr-axSpA or r-axSpA. Disease activity was measured using C-reactive protein (CRP) and the Ankylosing Spondylitis Disease Activity Score (ASDAS). Radiographic assessments of the cervical and lumbar spine were performed at baseline and after two years. Out of the initial 432 miRNAs, 90 met the selection criteria, and 45 were validated out of which miR-1-3p was upregulated, whereas miR-1248 and miR-1246 were downregulated in axSpA patients. The expression of miR-1-3p correlated with interleukin (IL)-17 and tumour necrosis factor (TNF) levels, indicating its significant role in axSpA pathogenesis. Although specific miRNAs distinguishing disease subtypes or correlating with disease activity or spinal changes were not found, the study identified three dysregulated miRNAs in axSpA patients, with miR-1-3p linked to IL-17 and TNF, underscoring its pathogenetic significance. These findings could help improve the early detection and treatment of axSpA.
Keywords: Axial spondyloarthritis; Biomarkers; miRNA; Profiling; Cytokines